2014
DOI: 10.1097/ta.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a surgical intensive care unit service is associated with improved outcomes for trauma patients

Abstract: Therapeutic/care management study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…This study illuminates the need to ensure that SCC training continues to be inclusive of non-trauma and also non-surgical conditions, for the purpose of maintaining a versatile and capable SCC workforce and sustaining the representation of surgical specialists in the world of critical care medicine. The specialty of SCC and management of patients in TICUs are geared toward the unique needs of surgical patients, and in some studies this narrow focus has demonstrated benefit in terms of lower ventilator days,3 complications,2–4 and mortality 4 5. This is consistent with evidence showing a survival benefit for patients treated in an ICU matched to their specific needs rather than boarding in another specialty unit 19.…”
Section: Discussionsupporting
confidence: 54%
“…This study illuminates the need to ensure that SCC training continues to be inclusive of non-trauma and also non-surgical conditions, for the purpose of maintaining a versatile and capable SCC workforce and sustaining the representation of surgical specialists in the world of critical care medicine. The specialty of SCC and management of patients in TICUs are geared toward the unique needs of surgical patients, and in some studies this narrow focus has demonstrated benefit in terms of lower ventilator days,3 complications,2–4 and mortality 4 5. This is consistent with evidence showing a survival benefit for patients treated in an ICU matched to their specific needs rather than boarding in another specialty unit 19.…”
Section: Discussionsupporting
confidence: 54%
“…There is limited data supporting the ability of specialized care teams to reduce morbidity to the same extent as mortality, HLOS, and total costs. 9, 11, 19 Additionally, one large prospective, multicenter study found a higher incidence of complications among trauma patients treated at trauma centers as compared to non-trauma centers. 20 Its authors hypothesized that more aggressive (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the trauma surgeon, privy to an inherent understanding of a patient's injury burden, may be at an advantage with respect to the decision to extubate. Klein et al 8 compared the outcomes of patients managed at a regional trauma center before and after the implementation of a surgical critical care service. Prior to the implementation of the service, the ICU care at their center was provided by a pulmonary medicine intensivist group.…”
Section: Discussionmentioning
confidence: 99%